KOMITMEN AFEKTIF ORGANISASI DITINJAU DARI PERSEPSI TERHADAP KEPEMIMPINAN TRANSAKSIONAL PADA PEKERJA PELAKSANA DI PERUSAHAAN UMUM (PERUM) X SEMARANG - Arviana Fitri Kusumastuti; Harlina Nurtjahjanti (Faculty of Economics and Business Diponegoro University, 2013)
Affective organizational commitment is a psychological attachment to the organization that is characterized by a strong desire of individuals to survive in an organization and there is emotional involvement of the organization, the identification of values and goals of the organization. The purpose of this study to determine the relationship between perceptions of transactional leadership style with affective organizational commitment in managing workers Perusahaan Umum (Perum) Perhutani Kesatuan Pemangkuan Hutan Semarang. The population in this study are workers implementing the Perusahaan Umum (Perum) Perhutani Kesatuan Pemangkuan Hutan Semarang. Study sample totaled 138 people, which is obtained through simple random sampling technique. Means of collecting data in this study is the scale. Affective and the scale of organizational commitment scale (32 valid aitem, α = 0.933) and perceptions of transactional leadership style (30 valid aitem α = 0.954), which has been tested on 38 workers implementing the Perusahaan Umum (Perum) Perhutani Kesatuan Pemangkuan Hutan Semarang. Data obtained by simple regression analysis demonstrated a correlation coefficient of 0.42 and p = (p <0.05). That is, there is a positive and significant relationship between two variables, if the more positive perceptions of transactional leadership style, the higher the affective commitment to the organizations, and conversely the more negative perceptions of transactional leadership style, the lower the affective organizational commitment in managing workers. These results indicate that the hypothesis is accepted. Perceptions of transactional leadership style contributed by 17.7% effective against affective organizational commitment, while 82.3% were influenced by other factors that are not revealed in the study. Keywords : Perception, Transactional leadership style, Affective organizational commitment